Bone Healing Using a Bi-Phasic Ceramic Bone Substitute Demonstrated in Human Vertebroplasty and with Histology in a Rabbit Cancellous Bone Defect Model - Hatten, H.P. (Centauro S.r.l., 2012)
A non-exothermic material that demonstrates clinical pain relief comparable to polymethylacrylate (PMMA) for vertebroplasty and promotes bone healing is desirable. The purpose of this investigation is to demonstrate clinical pain score improvement and bone healing following vertebroplasty with a novel bi-phasic ceramic cement. Twenty patients were prospectively treated for compression fractures in a single center in the USA with the injectable bi-phasic ceramic bone substitute. Statistical comparison of pain scores was made during a 12 month follow-up retrospectively against a matched cohort of patients treated with PMMA vertebroplasty by the same neuroradiologist (HPH) in the same setting. The bone remodeling material was also evaluated with histology in a New Zealand white rabbit model. The bi-phasic material demonstrated a pre-operative mean VAS score of 8.5 (± 1.6) with a significant post-operative pain relief mean VAS score of 1.8 (± 2.5) after one week, which was maintained throughout the 12 month follow-up period. These data are in line with the pain scores for the PMMA treated cohort. CT scans six and 12 months after surgery with the bi-phasic cement showed healing of the osteoporotic fractures. In the rabbit model, histology with the study material showed evidence of incorporation, new bone growth and bone healing in a cancellous bone defect. Both the clinical results and the histologic evidence of bone healing and new bone growth support the application of this new bioinjectable material as an alternative to the use of PMMA for vertebroplasty.